If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 89 = 7x + -74 Reorder the terms: 89 + 4x = 7x + -74 Reorder the terms: 89 + 4x = -74 + 7x Solving 89 + 4x = -74 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 89 + 4x + -7x = -74 + 7x + -7x Combine like terms: 4x + -7x = -3x 89 + -3x = -74 + 7x + -7x Combine like terms: 7x + -7x = 0 89 + -3x = -74 + 0 89 + -3x = -74 Add '-89' to each side of the equation. 89 + -89 + -3x = -74 + -89 Combine like terms: 89 + -89 = 0 0 + -3x = -74 + -89 -3x = -74 + -89 Combine like terms: -74 + -89 = -163 -3x = -163 Divide each side by '-3'. x = 54.33333333 Simplifying x = 54.33333333
| 3x+2=3x-3 | | 4h^2=-62h-30 | | 2x/3=15 | | 2x/3-9=32 | | (7x^2-3x-16)+(8x^2+8x)= | | 240x+35=5y+135x | | 3x^3=81 | | 6y=z | | 3(3e+2f)+yf+2=0 | | Y=5/2x+1 | | 4x+3x+5= | | 24+b=40 | | 38-y=250 | | 18+4y=2(3-y) | | c=P+3b+a | | 5/(b+5)-2/b | | 23x^2-15=6x | | 4/x=8/17 | | 9+4y=(3-y) | | -3(x+5)=2x+5 | | -4+5x=14-3x | | F(x)=2x-5 | | -18/-3 | | 34y+9=3(12y-18) | | 18x^3-9x^2-2x+1=0 | | 3+0.5x=4 | | x*0.3=460 | | F(3)=x+1 | | 21z=45-28z | | 2(x+3)=8x-18 | | 6y=(4y+18) | | 7-5(x+2)=3(x+2) |